The Characteristics of Sapindus Rarak Green Surfactant Injection to Enhance Oil Recovery - Fajri Maulida; Andrian Sutiadi; Muhammad Taufiq Fathaddin; Dwi Atty Mardiana; Rini Setiati; Pri Agung Rakhmanto; Arinda Ristawati; Sonny Irawan; Muhammad Dzaki Arkaan (Scientific Contributions Oil and Gas, 2024)
Green surfactants are surfactants derived from natural materials such as plants, animals, and microorganisms. Sapindus Rarak contains saponins, one type of natural surfactant that is widely known. This study evaluated the effectiveness of surfactant injection using Sapindus Rarak. This study involved laboratory experiments and analytical design with variations in salinity of 6,000 and 10,000 ppm and six variations of Sapindus Rarak surfactant concentrations from 0.5% to 3.0% using Berea sandstone cores at a temperature of 60℃. Compatibility testing based on water stability and phase behavior tests showed that only three samples of surfactant solutions, namely Sapindus Rarak surfactant concentration of 2.0% at a salinity of 6,000 ppm and surfactant concentrations of 2.5% and 3.0% at a salinity of 10,000 ppm, were homogeneous. The two best samples were selected based on the largest middle phase emulsion volume for each salinity, namely Sapindus Rarak surfactant concentration of 2.0% at a salinity of 6,000 ppm and surfactant concentration of 2.5% at 10,000 ppm. The wettability test of the two selected samples showed strongly water wet properties with contact angles of 26.86° and 23.28°, respectively. The results of the interfacial tension (IFT) test for the two selected samples were 2.15 x 10-1 and 1.71 x 10-1 mN/m, respectively. Based on the thermal stability test, the IFT values after 12 weeks for the two selected samples were smaller, namely 5.81 x 10-2 and 1.51 x 10-1 mN/m, respectively. Oil recovery factor (RF) for water injection showed that the use of 6,000 ppm salinity was better than 10,000 ppm salinity, which were 35.35% and 25.00%, respectively, while for surfactant flooding, the RF for the two selected Sapindus Rarak solution samples were 14.14% and 23.49%, respectively. This study offers a great opportunity to include green alternatives to improve conventional chemical-enhanced oil recovery techniques.